Quality of Life in Early‐Stage Oral Cancer: Interim Results from the COOLS Trial. (23rd August 2013) - Cromwell, Ian; Cressman, Sonya; Poh, Catherine; Durham, Scott; Rosin, Miriam P.; Peacock, Stuart
Abstract : Objectives: 1) Describe the quality of life experienced by oral cancer patients over time. 2) Explore subdimensions of quality of life over time. Methods: The pan‐Canadian Optically‐guided Oral Lesions Surgical (COOLS) Trial is a multi‐center randomized control trial evaluating a novel surgical staging method for the treatment of early‐stage oral cancer. Surveys were given to 92 participants at baseline, 6 weeks, and 3 months after surgery, collecting data on self‐reported quality of life (QoL). Results: Aggregate survey scores (EQ‐5D, FACT H&N) did not show much difference before or after surgery. Subscale analyses, however, revealed important differences in self‐reported pain, anxiety, and head/neck specific symptoms over time. Results are indicative of a recovery that happens over time, but it remains to be seen if this effect extends to the 12‐month follow‐up stage. QoL trajectory differs by surgical site, and the presence/absence of neck dissection. Selected relevant comparisons will be presented. Conclusions: At an aggregate level, surgery does not either improve or worsen QoL in early‐stage oral cancer patients; however, deeper examination of the data suggests that there are trends that will be clinically meaningful to patients and their families. These findings may help clinicians to better prepare their patients before surgery. Recovery to baseline QoL is achieved around 3 months, which suggests that surgery may improve long‐term (>12 month) QoL.